Terobosan Baru Transmisi Energi Listrik Tanpa Kabel - Masjono Muchtar (PROSIDING CSGTEIS 2013, 2013)
Abstract – Imagine that one day in the future every aspectof life conducted wirelessly including electricitydistribution. Wireles electricity transfer experiment has beenconducted at Lab Teknik Tenaga Listrik Akademi TeknikIndustri Makassar. Focus of this paper is to find thepossibility of using wireless power transfer system to lightenergy saving bulb wirelessly. Research methodologyconsists of literature studies, circuits design, contruction andtesting. The transmitter oscillator frequency was set to 1.645MHz. The result showed that the received power inverslyproportional with the distance between transmitter andreceiver. Instead of transferring electricity from transmiterto receiver, the transmitter able to light 10 watt energysaving bulb wirelessly.Keyword: wireless power transfer, witricity,electromagnetics.